Is it possible to welcome online? : Strategies and affections in remote classes of Portuguese as a welcoming language for Haitian immigrants during the pandemic - Pereira, Paula Graciano (2024)
In this work, we share experiences related to Portuguese as a Welcoming Language (PWL) classes during the period of the covid-19 pandemic in the Move Program of the Federal Institute of Education, Science, and Technology of Goiás. We reflect on the global migration crisis, the need to welcome immigrants, the theoretical and methodological aspects of PLAc teaching-learning, affectivity in the construction of welcoming, and strategies for these affective relationships in an online teaching-learning context. We analyzed how different strategies were used to establish positive affective relationships and build an educational welcoming environment and concluded that it is possible to welcome online as long as there is not only an attempt to transpose in-person attitudes to the virtual environment, but the understanding that welcoming goes beyond merely pedagogical actions and is built on the flow of affective relationships and interpersonal interactions, which can be mediated by digital tools.